2020
DOI: 10.4081/jphia.2020.1096
|View full text |Cite
|
Sign up to set email alerts
|

Modelling malaria reduction in a highly endemic country: Evidence from household survey, climate, and program data in Zambia

Abstract: Substantial efforts have seen the reduction in malaria prevalence from 33% in 2006 to 19.4% in 2015 in Zambia. Many studies have used effect measures, such as odds ratios, of malaria interventions without combining this information with coverage levels of the interventions to assess how malaria prevalence would change if these interventions are scaled up. We contribute to filling this gap by combining intervention coverage information with marginal predictions to model the extent to which key interventions can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Information on healthseeking behaviour among the population in the northwestern province with suspected symptoms of malaria is not available; however, it has been noted that the presence of chronic carriers of malaria parasites among the adult population may lead to underestimation of the true number of malaria cases in the population over the time period of the study [22]. Among the children under the age of five years, a national survey in 2015 found that only about 22% who had had a fever in the two weeks preceding the survey had sought treatment from health facilities [5]. Despite these limitations in available data, for planning purposes for those that seek medical care at health facilities, the monthly reported cases of confirmed malaria through the District Health Information System (DHIS) is helpful to health authorities.…”
Section: Study Areamentioning
confidence: 99%
See 3 more Smart Citations
“…Information on healthseeking behaviour among the population in the northwestern province with suspected symptoms of malaria is not available; however, it has been noted that the presence of chronic carriers of malaria parasites among the adult population may lead to underestimation of the true number of malaria cases in the population over the time period of the study [22]. Among the children under the age of five years, a national survey in 2015 found that only about 22% who had had a fever in the two weeks preceding the survey had sought treatment from health facilities [5]. Despite these limitations in available data, for planning purposes for those that seek medical care at health facilities, the monthly reported cases of confirmed malaria through the District Health Information System (DHIS) is helpful to health authorities.…”
Section: Study Areamentioning
confidence: 99%
“…Malaria remains a significant public health challenge in low and middle-income countries (LMICs) despite some advancements in diagnostic and treatment modalities and resources applied to prevention, control, and elimination [1][2][3]. Malaria is a disease caused by infection of parasites of Plasmodium species and transmitted through infected Anopheles mosquito bites [4,5]. However, though preventable and treatable, malaria continues to contribute significantly to global morbidity and mortality, especially in LMICs, mainly in sub-Saharan Africa, Latin America, and Asia [3,6,7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, governments need to monitor and enforce the implementation of malaria interventions ( 59 ). In Zambia, for example, many of the positive effects of control programs are being reduced by the negative impact of climatic conditions that favor the spread of malaria ( 60 ). These scenarios may lead to a more substantial resurgence, changes in seasonal trends, and complications for malaria control and elimination.…”
Section: Discussionmentioning
confidence: 99%